1986
DOI: 10.1523/jneurosci.06-09-02662.1986
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory synaptic drive for swimming mediated by amino acid receptors in the lamprey

Abstract: In order to investigate the properties and pharmacology of the excitatory synaptic drive received by motoneurons during swimming in the lamprey, propriospinal excitatory interneurons were activated as a population by the regional application of N-methyl-r+-aspartate (NMA) to either the 6-8 rostral-most or the 6-8 caudal-most segments of lengths of isolated spinal cord. This caused a rhythmic motor output to be generated in these regions. Synaptic potentials that were phase-locked to, and dependent on, the rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 27 publications
4
49
0
Order By: Relevance
“…To examine the effects of NO donors on ipsilateral excitatory synaptic transmission the recording chamber was divided into two pools by an agar barrier (Dale, 1986). Locomotor activity was induced in the rostral pool by NMDA (100 M) while the spinal cord in the caudal pool was perfused with physiological solution containing strychnine (5 M) to block inhibitory synaptic transmission.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the effects of NO donors on ipsilateral excitatory synaptic transmission the recording chamber was divided into two pools by an agar barrier (Dale, 1986). Locomotor activity was induced in the rostral pool by NMDA (100 M) while the spinal cord in the caudal pool was perfused with physiological solution containing strychnine (5 M) to block inhibitory synaptic transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of these amino acid receptors thus appears to be a prerequisite for the occurrence of locomotor activity under normal conditions (Brodin and Grillner, 1985a, b). Unitary synaptic potentials elicited by an activation of NMDA and kainate/ quisqualate receptors have recently been described in the lamprey spinal cord and furthermore it has been found that spinal interneurons acting via these excitatory amino acid receptors are of primary importance during fictive locomotion (Buchanan and Grillner, 1987;Dale, 1986). During fictive locomotion, many rhythmically active spinal neurons display well-developed membrane potential oscillations, phase-locked to the efferent ventral root bursts.…”
Section: Bath Applicationmentioning
confidence: 99%
“…In myotomal motoneurons the depolarizing peaks of the potential fluctuations occur in phase with the ipsilateral ventral root discharge Wallen, 1980, 1983;Buchanan and Cohen, 1982). They are due to synaptic activation of excitatory amino acid receptors of both the NMDA and kainate type (Dale, 1986).…”
Section: Bath Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two distinctive properties of the receptor, that it is both ligand and voltage gated (Engberg et al, 1979;MacDonald et al, 1982;Mayer et al, 1984;Nowak et al, 1984) and that its associated ionophore is more permeable to Ca2+ than to Na+ and K+ (Dingledine, 1983;Mayer and Westbrook, 1987) have each provoked particular interest among those concerned with its role in normal physiological function. The NMDA receptor has, for example, been implicated in the induction of hippocampal long-term potentiation (LTP) (Collingridge et al, 1983;Harris et al, 1984) and, more recently, in a variety of mechanisms including the coordination of rhythmic movements such as swimming (Dale, 1986(Dale, , 1989) sensory transduction (Fox et al, 1989;Sillito et al, 1990) developmental plasticity (Bear et al, 1987;Kleinschmidt et al, 1987;McDonald and Johnston, 1990;Singer, 1990); and learning (Morris et al, 1986). Its highest density, however, is in the hippocampus (Monaghan et al, 1983;Monaghan and Cotman, 1985) an area associated with certain forms of learning (O'Keefe and Nadel, 1978;Olton et al, 1979;Squire, 1987).…”
mentioning
confidence: 99%